Diversity of Oligopeptide Transport in Yeast and Its Impact on Adaptation to Winemaking Conditions - Becerra-Rodríguez, Carmen; Marsit, Souhir; Galeote, Virginie (Frontiers in Genetics, 2020)
Nitrogen is an essential nutrient for yeasts and its relative abundance is an important modulator of fermentation kinetics. The main sources of nitrogen in food are ammonium and free amino acids; however, secondary sources such as oligopeptides are also important contributors to the nitrogen supply. In yeast, oligopeptide uptake is driven by different families of proton–coupled transporters whose specificity depends on peptide length. Proton-dependent Oligopeptide Transporters (POT) are specific to di- and tripeptides, whereas the Oligopeptide Transport (OPT) family members import tetra- and pentapeptides. Recently, the novel family of Fungal Oligopeptide Transporters (FOT) has been identified in Saccharomyces cerevisiae wine strains as a result of a horizontal gene transfer from Torulaspora microellipsoides. In natural grape must fermentations with S. cerevisiae, Fots have a broader range of oligopeptide utilization in comparison with non-Fot strains, leading to higher biomass production and better fermentation efficiency. In this review we present the current knowledge on the diversity of oligopeptide transporters in yeast, also discussing how the consumption of oligopeptides provides an adaptive advantage to yeasts within the wine environment.